PREDICTION OF FINANCIAL DISTRESS IN SELECTED FMCG COMPANIES USING THE ALTMAN Z-SCORE MODEL - Gorkhe, Monika Dasharath; Khartode, Asmita Satish (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Financial statement analysis has played a crucial role in evaluating a company's potential for financial difficulties, such as its ability to repay debts. Initially, credit suppliers utilized financial statement analysis to assess the creditworthiness of borrowers. However, in today's landscape, financial statement analysis has become widespread, involving a diverse range of ratios and catering to various users which include the suppliers, commercial banks, agencies involved in credit rating, existing and potential investors, higher management and others. Financial distress denotes to a company's incapacity to meet its financial commitments as they come due. Academic research in accounting and finance has predominantly emphasized defaulters of bond holders or bankruptcy as indicators of distress. The primary question revolves around whether the likelihood of distress significantly fluctuates based on the magnitude of financial statement ratios. This research study analyses the how sound the financial health of the company is and what are the probabilities of bankruptcy of selected companies belonging to the FMCG sector in India with the help of revised Altman Z-score model. This study focuses on the analysis of twenty (20) selected Fast Moving Consumer Goods (FMCG) companies listed on the Stock Index i.e Bombay Stock Exchange (BSE). These companies represent various segments such as Personal care, Food and Beverages, Alcohol and Cigarettes, Dairy, Food, Soaps and Detergents, Tobacco products, home care and other consumer durables. Based on the study's findings, it can be inferred that a majority of the companies in the FMCG sector in India exhibit good financial health and fall within the Safe Zone according to the Altman Z score model. The companies initially classified in the grey zone have shown improvements in their financial well-being in subsequent years. The Pearson correlation analysis reveals a noteworthy positive relationship between the variables and the Altman Z scores. Consequently, the study validates the effectiveness of the Altman Z score model as a reliable tool for predicting and forecasting the level of and impact of financial distress in companies. Emphasizing both the analytical and practical significance, this study aims to showcase the inherent value of using financial ratios. By employing financial ratios, this research underscores their potential to provide meaningful insights and practical applications in assessing corporate performance. As a result, investors can utilize this study to identify financially stable companies and make informed investment decisions based on the findings.